2014
DOI: 10.1007/s13197-014-1307-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different calcium sources on the bioactive compounds stability of extruded and nixtamalized blue maize flours

Abstract: The stability of antioxidants in extruded and nixtamalized blue maize flours with calcium hydroxide [Ca(OH) 2 ] and calcium lactate [C 6 H 10 O 6 Ca] were evaluated. Extruded blue maize flours batches were obtained by mixing blue maize flours separately with different Ca(OH) 2 (0.1, 0.2 and 0.3 %) and C 6 H 10 O 6 Ca (0.3, 0.6 and 0.9 %) concentrations respectively and extruded to obtain the extruded flours. For nixtamalized flours, the maize grains were cooked at 1 % Ca(OH) 2 and 2.95 % C 6 H 10 O 6 Ca concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
3
20
2
2
Order By: Relevance
“…Values are mean ± SD (n = 4), on a dry matter basis. Although in this study individual anthocyanins were not identified, we suggest that cyanidin 3-glucoside is the main pigment in blue tortillas because it has been reported as the major anthocyanin in blue maize foods (Del Pozo-Insfran et al 2006;Sánchez-Madrigal et al 2014). EP = extractable polyphenols; HP = hydrolyzable polyphenols; CT = condensed tannins; DPPH = 1,1-diphenyl-2picrylhydrazyl; ABTS = 2,29-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid); and FRAP = ferric reducing antioxidant power.…”
Section: Figmentioning
confidence: 54%
“…Values are mean ± SD (n = 4), on a dry matter basis. Although in this study individual anthocyanins were not identified, we suggest that cyanidin 3-glucoside is the main pigment in blue tortillas because it has been reported as the major anthocyanin in blue maize foods (Del Pozo-Insfran et al 2006;Sánchez-Madrigal et al 2014). EP = extractable polyphenols; HP = hydrolyzable polyphenols; CT = condensed tannins; DPPH = 1,1-diphenyl-2picrylhydrazyl; ABTS = 2,29-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid); and FRAP = ferric reducing antioxidant power.…”
Section: Figmentioning
confidence: 54%
“…z Different letters within each column indicate significant differences (P < 0.01). Several studies have investigated the phenolic composition and AOX of nixtamalized extruded products such as tortillas and tortilla chips, and these products comparatively contained higher amounts of these compounds compared with counterparts produced from regular nixtamalized flours (Mora-Rochin et al 2010;Aguayo-Rojas et al 2012;Sánchez-Madrigal et al 2014). ENF = extruded nixtamalized corn flour, and ENBESB = ENF and sorghum bran (SB) added before extrusion.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have previously studied the fate of phytochemicals during the sequential steps of the traditional nixtamalization process (Corrales‐Bañuelos et al, ; Mora‐Rochin et al, , ; de la Parra, Serna, & Liu, ; Sánchez‐Madrigal et al, ). Corn tortillas are elaborated mainly with white maize that contains lesser amounts of ferulic acid (FA) (21.42%) and lipophilic antioxidant activity (45.91%) (Mora‐Rochin et al, ) compared to pigmented counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Corn tortillas are elaborated mainly with white maize that contains lesser amounts of ferulic acid (FA) (21.42%) and lipophilic antioxidant activity (45.91%) (Mora‐Rochin et al, ) compared to pigmented counterparts. Nowadays, tortillas made with pigmented maize genotypes (yellow, high‐carotenoid, blue, or red) are also consumed, mainly for their health benefits (Corrales‐Bañuelos et al, ; Mora‐Rochin et al, , ; de la Parra et al, ; Sánchez‐Madrigal et al, ). It has been reported that pigmented tortillas contain lesser amounts of FA (34.92%–39.10%), lipophilic antioxidant activity (63.77%–80.76%), anthocyanins (10.07%–46%) (Mora‐Rochin et al, , ), and carotenoids (72%–87.6%) (Corrales‐Bañuelos et al, ) compared to amounts assayed in raw kernels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation